2006
DOI: 10.1016/j.jacc.2006.06.071
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Left Ventricular Function by Cardiac Ultrasound

Abstract: Our understanding of the physical underpinnings of the assessment of cardiac function is becoming increasingly sophisticated. Recent developments in cardiac ultrasound permit exploitation of many of these newer physical concepts with current echocardiographic machines. This review will first focus on the current approach to the assessment of cardiovascular hemodynamics by cardiac ultrasound. The next focus will be the assessment of global cardiac mechanics in systole and diastole. Finally, relationships betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
135
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(136 citation statements)
references
References 123 publications
(86 reference statements)
0
135
1
Order By: Relevance
“…[14][15][16] It has been shown that delayed and reduced diastolic untwisting during the diastolic phase may be an early indicator of an LV relaxation abnormality for hypertensive patients with LV hypertrophy. 17 Bansal et al 5 found that resting global LVrot and regional LVrot were significantly reduced in patients with myocardial infarction compared to those without previous myocardial infarction, and LVrot was most impaired in patients with multiple areas of infarction.…”
Section: Left Ventricular Rotation and Clinical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] It has been shown that delayed and reduced diastolic untwisting during the diastolic phase may be an early indicator of an LV relaxation abnormality for hypertensive patients with LV hypertrophy. 17 Bansal et al 5 found that resting global LVrot and regional LVrot were significantly reduced in patients with myocardial infarction compared to those without previous myocardial infarction, and LVrot was most impaired in patients with multiple areas of infarction.…”
Section: Left Ventricular Rotation and Clinical Implicationsmentioning
confidence: 99%
“…Therefore, LVrot assessment represents an interesting approach for quantifying LV function and may provide important clinical information about cardiac function. 6,15 Current Clinical Techniques for Measuring LVrot Left ventricular rotation can be measured noninvasively using both MRI and echocardiography. Tagged MRI has been considered the reference standard for noninvasive LVrot assessment.…”
Section: Left Ventricular Rotation and Clinical Implicationsmentioning
confidence: 99%
“…Tissue Doppler imaging (TDI) is one of the more recent technological advances that allows quantitative characterization of regional wall motion velocities 3, 4. Both in people and in small animals, the clinical applicability of TDI has been established and the modality has been successfully applied for the assessment of systolic and diastolic LV function and estimation of ventricular filling pressures 4, 5, 6, 7.…”
mentioning
confidence: 99%
“…Thomas and Popovic have reviewed the clinical application of LV strain imaging using tissue Doppler derived and speckle tracked derived strain imaging for evaluation of regional myocardial function. 8 Abnormal LV strain (> -20) can be used to determine subclinical systolic dysfunction. Left ventricular strain imaging with 2-D speckle tracking is done frequently in many labs to evaluate patients for subclinical LV systolic dysfunction when overall LV ejection fraction is preserved, especially in condition like amyloidosis and hypertrophic cardiomyopathy.…”
Section: Aliakbar Arvandi MDmentioning
confidence: 99%